Bismuth–nickel bimetal nanosheets with a porous structure for efficient hydrogen production in neutral and alkaline media. Issue 46 (27th October 2022) - Yu, Xueping; Qu, Li; Lee, Carmen; Peng, Juan; Yan, Qingyu; Bai, Hongcun; Yao, Min
Abstract : A Bi–Ni bimetal nanosheet with mesoporous structure is prepared via a self-template electrochemical in situ method. The alloying effect between Bi and Ni regulated the electronic structure, thus improving the intrinsic activity of Bi–Ni catalyst. Abstract : Active and durable electrocatalysts are very important for efficient and economically sustainable hydrogen generation via electrocatalytic water splitting. A bismuth–nickel (Bi–Ni) bimetal nanosheet with a mesoporous structure was prepared via a self-template electrochemical in situ process. The Bi–Ni catalyst required overpotentials of 56 mV and 183 mV at 10 mA cm −2 for the hydrogen evolution reaction (HER), which were close to that of commercial Pt/C in 1.0 M KOH and 1.0 M PBS (pH 7.0), respectively. The electrocatalyst maintained a steady current density during 20 h electrolysis in 1.0 M KOH and 1.0 M PBS (pH 7.0). Density functional theory (DFT) indicated that the alloying effect could induce charge transfer from the Bi atom to Ni atom and thus modulate the d-band centre of Bi–Ni nanosheets, which could efficiently accelerate H* conversion and H2 desorption at the Ni active site. This promotes the HER kinetics. By adopting the Bi84.8 Ni15.2 alloy as the cathode to establish a full-cell (IrO2 ∥Bi84.8 Ni15.2 ) for water splitting in 1.0 M KOH, the required cell voltage was 1.53 V to drive 10 mA cm −2, which was lower than that of the IrO2 ∥Pt/C electrolyzer (1.64 V@10 mA cm −2 ).